Mechanisms underlying the anti-inflammatory effects of Clinacanthus nutans lindau extracts: inhibition of cytokine production and Toll-like receptor-4 activation - Mai, Chun Wai; Yap, Ivan Kok Seng; Kho, Mee Teck; Ismail, Nor Hadiani; Yusoff, Khatijah; Shaari, Khozirah; Chin, Swee Yee; Lim, Swee Hua Erin (Frontiers Research Foundation, 2016)
Clinacanthus nutans has had a long history of use in folk medicine in Malaysia and Southeast Asia; mostly in the relief of inflammatory conditions. In this study, we investigated the effects of different extracts of C. nutans upon lipopolysaccharide (LPS) induced inflammation in order to identify its mechanism of action. Extracts of leaves and stem bark of C. nutans were prepared using polar and non-polar solvents to produce four extracts, namely polar leaf extract (LP), non-polar leaf extract (LN), polar stem extract (SP), and non-polar stem extracts (SN). The extracts were standardized by determining its total phenolic and total flavonoid contents. Its anti-inflammatory effects were assessed on LPS induced nitrite release in RAW264.7 macrophages and Toll-like receptor (TLR-4) activation in TLR-4 transfected human embryonic kidney cells (HEK-BlueTM-hTLR4 cells). The levels of inflammatory cytokines (TNF-α, IFN-γ, IL-1β, IL-6, IL-12p40, and IL-17) in treated RAW264.7 macrophages were quantified to verify its anti-inflammatory effects. Western blotting was used to investigate the effect of the most potent extract (LP) on TLR-4 related inflammatory proteins (p65, p38, ERK, JNK, IRF3) in RAW264.7 macrophages. All four extracts produced a significant, concentration-dependent reduction in LPS-stimulated nitric oxide, LPS-induced TLR-4 activation in HEK-BlueTM-hTLR4 cells and LPS-stimulated cytokines production in RAW264.7 macrophages. The most potent extract, LP, also inhibited all LPS-induced TLR-4 inflammatory proteins. These results provide a basis for understanding the mechanisms underlying the previously demonstrated anti-inflammatory activity of C. nutans extracts.